Penerapan Teknik Ice Breaking untuk Meningkatkan Motivasi Belajar Ekonomi di Kelas XII IPS SMAN 3 Kayuagung - Herlina Herlina (UNDIKMA, 2022)
This study aims to increase the motivation to learn the economics of class XI IPS students at SMAN 3 Kayuagung through the application of ice breaking techniques. The research method used is classroom action research conducted in two cycles. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. The data collection technique in this research used observation sheets and tests, then the data were analyzed descriptively. The results showed that the activities of students and student learning outcomes increased in each cycle, namely in the first cycle, students' learning activities increased by 60% to 85%. and learning completeness reached 62.07%. While in Cycle II the learning activities of students were 90% to 97% and learning completeness reached 89.66%. So the conclusion of this research is that the application of ice breaking technique can increase learning motivation and learning outcomes of XII IPS students of SMAN 3 Kayuagung.